Energy-Efficient Bus and Tram Networks: Innovations in Urban ‎Transit Solutions - Soy , Aakansha; Nayak , Ashu (International Journal of Basic and Applied Sciences, 2025)
Public transportation is a major source of energy usage; thus, it is crucial to transform bus/tram systems into low-carbon systems to achieve ‎the goal of sustainable cities. This paper aims to discuss various strategies that help improve the energy efficiency of PTs with reliability and ‎accessibility guarantees. Here, it looks at perpetual motion like electric and hybrid buses, environmentally friendly technologies like ‎regenerative braking systems, light-weight materials, and intelligent charging systems. Further, the use of renewable energy generation, such ‎as solar and wind, and the use of energy management systems is also explained. This paper also assesses operational tactics, including AI-based path finding, monitoring, and environmentally conscious driving to minimize energy loss. Refers to policy guidelines and government ‎support are emphasized, and examples of policy implementation include Shenzhen city in China and Freiburg city in Germany. Therefore, ‎the study supports and stresses the fact that energy-efficient transit networks are pivotal for attaining sustainability in urban regions. The ‎paper concludes with the practical steps various urban planners and policymakers can take to overcome such factors as high initial costs, ‎infrastructure improvements, and acceptance by the public to enhance the use of energy-efficient measures‎.